2018
DOI: 10.1371/journal.pone.0194443
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Escherichia coli strains encoding colibactin isolated from immunocompromised mice with urosepsis and meningitis

Abstract: Immune-compromised mouse models allow for testing the preclinical efficacy of human cell transplantations and gene therapy strategies before moving forward to clinical trials. However, CRISPR/Cas9 gene editing of the Wsh/Wsh mouse strain to create an immune-compromised model lacking function of Rag2 and Il2rγ led to unexpected morbidity and mortality. This warranted an investigation to ascertain the cause and predisposing factors associated with the outbreak. Postmortem examination was performed on 15 moribund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 52 publications
3
12
0
Order By: Relevance
“…We used the E. coli K-12 strain, which is psk-, and the pks + strain NC101 to infect the adenocarcinoma cell line Caco-2 and assessed cytotoxicity through the megalocytosis assay. As expected (25), Fig. 4A shows that cells infected with E. coli NC101 displayed enhanced megalocytosis compared to cells infected with the control E. coli K-12 strain.…”
Section: Oligosaccharides Increase Colibactin-induced Cytotoxicity Ansupporting
confidence: 81%
“…We used the E. coli K-12 strain, which is psk-, and the pks + strain NC101 to infect the adenocarcinoma cell line Caco-2 and assessed cytotoxicity through the megalocytosis assay. As expected (25), Fig. 4A shows that cells infected with E. coli NC101 displayed enhanced megalocytosis compared to cells infected with the control E. coli K-12 strain.…”
Section: Oligosaccharides Increase Colibactin-induced Cytotoxicity Ansupporting
confidence: 81%
“…C57BL/6 c-Kit W–sh (B6.Cg- Kit W–sh /HNihrJaeBsmJ, Stock No:030764) mice were obtained from the Jackson Laboratory and maintained in the WI animal facility which is affiliated with Massachusetts Institute of Technology (Cambridge, MA, USA). C57BL/6 Il2rg −/– Rag2 −/– cKit W–sh mice, which is represented by B6.Il2rRag2W throughout the text, were generated via one-cell embryo injection of Cas9 mRNA and sgRNA into C57BL/6 c-Kit W–sh mice as previously described [ 8 ]. Additional laboratory mouse strains/stocks used in the present study included immunodeficient NSG (NOD.Cg- Prkdc scid Il2rg tm1Wjl /SzJ, Stock No: 001976) and immunocompetent UTX flox (B6;129S- Kdm6a tm1.1Kaig /J, stock No:024177) from Jackson Laboratory and Crl:CD1(ICR) mice from Charles River Laboratories.…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported the occurrence of a sudden increase in morbidity and mortality in a colony of B6.Il2rRag2W mice associated with pks + E. coli-induced urosepsis and meningitis [8]. Retrospective evaluation of the kidneys from 14 of 15 B6.Il2rRag2W mice (5.5-22 months old) in this study [8] confirmed the presence of interstitial fibrosis and intranuclear inclusion bodies in convoluted tubules in 10 of 14 mice; these lesions are consistent with IBN described recently [5]. An additional 10 B6.Il2rRag2W mice (3.5-10 months old) submitted for necropsy after the pks+ E. coli outbreak also had IBN.…”
Section: Mkpv Is Associated With Ibn In a Colony Of B6il2rrag2w Micementioning
confidence: 99%
See 1 more Smart Citation
“…As such, the prevalence of cyclomodulin-encoding E. coli in laboratory marmosets is currently unknown. We hypothesized that common marmosets, similar to laboratory rodents and other laboratory nonhuman primates 25 29 , are colonized by cyclomodulin-encoding E. coli , and the prevalence of pks +, cnf +, and cdt + E. coli in our population would vary significantly depending on the colony of origin, as has been demonstrated in laboratory rats 28 . In addition, we hypothesized that pks +, cnf +, and cdt + E. coli are present in animals afflicted with gastrointestinal disease with greater frequency than in clinically normal animals.…”
Section: Introductionmentioning
confidence: 97%